ESTABLISHMENT AND DEVELOPMENT OF EDUCATION IN POLAND AT THE BEGINNING OF XІ – IN THE END OF XVI CENTURY - Hryshchuk Yuliіa V. (Educological discourse, 2016)
The article examines the establishment and development of education in Poland at the beginning of XI – in the end of XVI century; analyzed the impact of socio-political and socio-economic factors on the formation and development of education in Poland. It has been established that the most important thing for the development of higher education in Poland were establishment and functioning of the Krakow University – Research Center for training teachers and other staff.